Application of spectroscopy technology for nutrient monitoring in cocoa plantation: a review - Mat Nawi, Nazmi; Jahari, Mahirah; Wong, Mui Yun; Madian, Nurfadzilah (Malaysian Cocoa Board, 2024)
The fundamental component of food security is adapting agricultural systems to sustenance production improvements and reducing inputs and the negative consequences of climate change. Precision agriculture developments in recent years have considerably boosted the efficacy of managing spatially variable agronomic irrigation inputs such as pesticides, seeds, water and fertilizers. The growing number of innovations using cutting-edge technologies to monitor field crop for varied temporal and spatial changes is responsible for these advancements. This review compares the applicability, cost, limitations, and advantages of using spectroscopy technology for nutrient monitoring in cocoa plantations with conventional methods. This paper highlights basic information on cocoa crops, then focuses on fertilizer applications, and management in each of the chosen cocoa-producing countries. Concerns about the nutrient adequacy of the soil and the monitoring of nutrient availability in the soil and leaves by using conventional and Near-Infrared Spectroscopy (NIRS) are discussed. The limitations of the conventional analysis method and technology of NIRS are also discussed. A general overview of how each of these sectors benefits from the use of NIRS, along with specific applications related to each sector, is also presented. Therefore, we briefly present the advantages of this technology and demonstrate its potential for nutrient monitoring in cocoa plantations.